THE EFFECT OF USING FERMENTED BANANA PEELS IN RATIONS ON PHYSICAL COMPOSITION OF CARCASS AND ABDOMINAL FAT DISTRIBUTION OF JOPER CHICKEN - C., Simamora; Puger, A. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
The objective of this study was to determine the effect of using fermented banana peels in feed rations on physical composition of carcass and fat distribution of Jowo and Super (Joper) native chicken.  The design used was completely randomized design (CRD) with 4 treatments and 5 replications.  Each replication used 3 joper chickens with 2 weeks of age. The treatments consisted of ration without fermented banana peels (TP) as a control, the using of fermented banana peels in ration with 3%, 6% and 9% concentrations as P1, P2, and P3.  The result of this study showed that the using of fermented banana peels ( Musa paradisiaca L. var sapientum ) with the 6% concentration gave the highest and most significant average (P<0,05) on physical composition of carcass, final body weight, carcass weight and meat weight.  Fat distribution was not significally different in all treatments (P>0,05).  Based on the result of this study, it can be concluded that the using of fermented banana peels in rations with maximal concentration 6% can increase physical composition of joper chicken carcass, on the variable of final body weight, carcass weight, and meat weight.  Fermented banana peels in ration has not been able to affect the physical composition of Joper chicken carcass on the variable of bone percentage and skin percentage.  Fermented banana peels has not affected the component of Joper chicken abdominal fat. Keywords: joper chicken, fermented banana peel, carcass, abdominal fat